Synthesis and Biomedical Applications of Lanthanides-Doped Persistent Luminescence Phosphors With NIR Emissions - Qin, Xinyuan; Wang, Jie; Yuan, Quan (Frontiers in Chemistry, 2020)
Persistent luminescence phosphors (PLPs) are largely used in biomedical areas owing to their unique advantages in reducing the autofluorescence and light-scattering interference from tissues. Moreover, PLPs with long-lived luminescence in the near-infrared (NIR) region are able to be applied in deep tissue bioimaging or therapy due to the reduced light absorption of tissues in NIR region. Because of their abundant election levels and energy transfer channels, lanthanides are widely doped in PLPs for the generation of NIR persistent emissions. In addition, the crystal defects introduced by lanthanides-doping can serves as charge traps in PLPs, which contributes to the enhancement of persistent luminescence intensity and the increase of persistent time. In this paper, the research progress in the synthesis and biomedical applications of lanthanides-doped PLPs with NIR emissions are systematically summarized, which can provide instructions for the design and applications of PLPs in the future.